Evaluation criterion of flow fields in PEM fuel cells based on entropy generation analysis. (19th January 2023) - Ding, Quan; Zhu, Kai-Qi; Xu, Jiang-Hai; Zhang, Ben-Xi; Yang, Yan-Ru; Yang, Chen; Wang, Yu-Lin; Lee, Duu-Jong; Wan, Zhong-Min; Wang, Xiao-Dong
Abstract: Two geometrical parameters, amplitude and wavelength, of the structure of the wavy-flow field in a proton exchange membrane fuel cell (PEMFC) were investigated on their impacts on cell performances via a three-dimensional, multiphase, and non-isothermal model. Amplitude and wavelength significantly influence oxygen transport, friction resistance, and current densities in PEMFC operations. The enhancement of current density peaks at an amplitude of 0.4 mm and a wavelength of 2 mm, increased by 10.40% compared to the non-wavy design. The wavy channels would increase the oxygen concentration gradient and the viscous friction, increasing entropy generation. The entropy generation rates increase more significantly at small wavelengths and large amplitudes. The entropy generation ratio (EGR) evaluates the performances of different wavy channels based on the accurate description of oxygen transport in PEMFC without calculating the associated pumping power consumption rates. The EGR decreases with decreasing wavelength or increasing amplitude. Highlights: Entropy generation by mass transport and friction is greatly influenced by flow field types. The entropy generation analysis is introduced to verify the superiority of flow fields. EGR is proposed for the evaluation of oxygen transport under unequal pumping power consumptions.